2021
DOI: 10.4315/jfp-20-399
|View full text |Cite
|
Sign up to set email alerts
|

Detection of β-Lactamase–Producing Proteus mirabilis Strains of Animal Origin in Andhra Pradesh, India and Their Genetic Diversity

Abstract: Proteus mirabilis is abundantly found in soil and water, and although it is part of the normal human intestinal flora, it has been known to cause serious infections in humans and a common pathogen responsible for complicated urinary tract infections. It is also commonly associated with multidrug resistance. In the current study, analysis of 1093 different samples from foods of animal origin and intestinal samples confirmed 232 P. mirabilis isolates by PCR. Of the 232, 72 isolates exhibited β-lactamase producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This can be a drawback of the current study. A recent study showed that 5.63% pork samples were contaminated with P. mirabilis producing β-lactamase [35]. However, all P. mirabilis isolated in the study were susceptible to β-lactams.…”
Section: Discussionmentioning
confidence: 60%
“…This can be a drawback of the current study. A recent study showed that 5.63% pork samples were contaminated with P. mirabilis producing β-lactamase [35]. However, all P. mirabilis isolated in the study were susceptible to β-lactams.…”
Section: Discussionmentioning
confidence: 60%
“…The species isolated in the second sampling are generally less virulent and less pathogenic for the udder, except, of course, for the Staphylococcus aureus and the Staphylococcus haemolyticus , which are involved in the pathogenesis of mastitis. Streptococcus parasanguinus is rarely pathogenic for the udder and the same holds true for Streptococcus pluranimalium [ 79 ] and for Proteus mirabilis , which is known to cause cystitis and pyelonephritis and is present in soil and water [ 80 ]. Veillonella parvula is not able to ferment carbohydrates and lives on the lactate produced by Streptococci [ 81 , 82 ], so it is reasonable to assume that this bacterium was rather isolated due to the isolation of the aforementioned Streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…isolates harbored the blaTEM gene [21]. In India, the blaTEM rate among P. mirabilis isolates was 81.9% [22], while in Egypt, it was 35% [23]. In Tehran, Iran, Malekjamshidi et al (2010) estimated blaTEM prevalence at 83% among ESBL-positive specimens [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hamid et al, no P. mirabilis isolates in Iraq had blaSHV [19]. In India, the blaSHV prevalence among P. mirabilis isolates was 7% [22]. In Tehran, Iran, the prevalence of blaSHV prevalence was 8% in ESBL-positive P. mirabilis isolates [24] The correlation between blaTEM and blaSHV gene and resistance to some antibiotics showed a significant correlation.…”
Section: Discussionmentioning
confidence: 99%